Cost assessment of elasticity for a 5G broadband network. Issue 4 (13th December 2021) - Rendon Schneir, Juan; Bradford, Julie; Konstantinou, Konstantinos; Sumanasena, Abhaya; Zimmermann, Gerd; Gramaglia, Marco
Abstract: In the highly competitive telecommunications market, operators need to consider techniques that might lead to a more cost‐efficient use of the network resources. The recently proposed concept of resource elasticity focuses on the inherent cost reductions achieved by tailoring the resource utilization of network elements, such as radio and cloud elements, to the real network demand. However, no research has been conducted so far regarding the cost benefits that such schemes could bring to 5G networks, in terms of total cost of ownership. This article makes a novel contribution by analyzing the cost benefits of employing elasticity in a 5G network providing users with a broadband service in a hotspot area. The area exemplarily analyzed was the Port of Hamburg in Germany, which is a realistic scenario and which receives a considerable number of additional mobile users when a cruise ship arrives at the port. The results show that, for the different scenarios analyzed, the total radio access network cost reductions of using elasticity compared to a non‐elastic network range from 2.5% to 4.4%. Considering the edge cloud site‐related cost component alone, a 16.4% saving from elasticity was found. Further research is needed to understand the benefits of elasticity for other types of 5G use cases in different types of areas. Abstract : This article makes a novel contribution by analyzing the cost benefits of employing elasticity for a 5G network that provides users with a broadband service in a hotspot area. The total CAPEX and OPEX achieved by the employment of elasticity compared to a non‐elastic network range from 2.5% to 4.4%.